Jabatan Kerja Raya project delivery excellence through effective project communication management - Abd. Hamid, Noorhayati (2015)
The purpose of this study is to identify the process of communication management that is being practiced currently in JKR in project life-cycle to produce an excellence project delivery. The objectives of this study are to identify client perception regarding to process of effective communication management and also to identify client’s perception in regard to effective project delivery excellence. Other objective in this study is to examine relationship between effective communication management and project delivery excellence and also to examine the influence of effective communication management toward project delivery excellence faced by JKR regarding project communication management during it course of project implementation delivery stage. Location of the study is in JKR Headquarters. The methodology use for this study is survey by distributing a set of questionnaires to 80 respondents at the Kementerian Kesihatan Malaysia, Head of Design Team (HODT), Consultants and Contractors by hand, by email and by online. Data gathered from questionnaire was analyzed using descriptive statistic (mean, percentage and standard deviation) and inferential statistic (Pearson Correlation and Multiple Regression). The overall mean for communication (4.0407) falls into range 3.68-5.00 which is high and mean for delivery was (3.9975) falls into range 3.68-5.00 which also high. The result for correlation shows that has a moderate correlation between effective communication and project delivery excellence which is 0.407 and correlation is significant at the 0.01 level (2-tailed). The R² indicates that communication contribute 16.6% to project delivery excellence. Based on the Statistic F = 14.680 significant shows there is a relationship between communication and project delivery excellent. Significant Beta coefficient for communication management ß = 0.407 shows that communication management influence project delivery. If communication management is increased by 1 unit, project delivery excellence will increase 0.4 units.